OPPORTUNITIES FOR RESEARCH KNOWLEDGE AND DEVELOPMENT OF REFLEXIVE ACTIVITIES THROUGH QUEST TECHNOLOGY IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Scientific journal of the Fergana State University, 2024)
The article will talk about the organization of educational activities on the basis of “state requirements for the development of children of Primary and preschool age”, which is considered the main document in preschool educational organizations, and the need to develop research and reflexive activities of children in these processes, the formation of these skills, the urgent importance of Quest technology. The article recognizes quest technology as an effective methodology in the formation of research cognition and reflexive activity in young children.